Ferrite-martensite duplex stainless steel with excellent bendability and method for producing same

A specific multi-phase stainless steel composition and manufacturing process enhance bendability and reduce costs by maintaining a high martensitic phase ratio and reducing carbide size, addressing cracking risks and eliminating additional heat treatments.

JP7618443B2Active Publication Date: 2025-01-21NIPPON STEEL CORPORATION
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020215694
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-01-21
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Existing multiphase stainless steels face issues with bendability and high manufacturing costs due to the risk of cracking during bending and the need for additional heat treatment processes.

Method used

A multi-phase stainless steel composition with a specific range of elements and a manufacturing process involving a short multi-phase heat treatment at 800-1000°C for less than 1 minute, followed by rapid cooling, to maintain a high martensitic phase ratio and reduce carbide size, enhancing bendability without additional heat treatments.

Benefits of technology

The solution results in a stainless steel with improved bendability and reduced manufacturing costs by maintaining strength and ductility while minimizing the risk of cracking and eliminating the need for extra heat treatment steps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618443000003
    Figure 0007618443000003
  • Figure 0007618443000004
    Figure 0007618443000004
  • Figure 0007618443000005
    Figure 0007618443000005
Patent Text Reader

Abstract

To provide a double-phase stainless steel that has improved bendability, and to provide a method for producing the same.SOLUTION: A stainless steel contains, in mass%, C by 0.01 to 0.2%, Si by 0.01 to 2.0%, Mn by 0.1 to 4.0%, P by 0.05% or less, S by 0.03% or less, Cr by 10 to 20%, Ni by 0.01 to 4.0%, N by 0.12% or less, and O by 0.01% or less, includes ferrite phase and martensite phase, has a hardness of 200 to 340 HV, and, in the cross section, the area ratio of the martensite phase is 60 to 75%, the area ratio of carbide is 0.5 to 1.5%, and the major axis of the carbide is 1 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic-martensite duplex stainless steel having excellent bendability and a method for producing the same. [Background technology]

[0002] Martensitic stainless steel, which has been quenched and tempered to increase its hardness, is known as a type of stainless steel with improved strength, but this martensitic stainless steel has a problem of low ductility.

[0003] To address this problem, for example, a multi-phase heat treatment technique is known to ensure both ductility and strength. For example, Patent Document 1 describes a method for producing a high-ductility, high-strength multi-phase chromium stainless steel sheet by performing a multi-phase heat treatment on a cold-rolled stainless steel sheet.

[0004] Patent Document 2 describes a method for producing a high-strength, dual-phase stainless steel strip with excellent spring properties, in which a cold-rolled stainless steel strip is subjected to a dual-phase heat treatment to produce a steel strip with a mixed structure of ferrite and martensite, and the steel strip is then subjected to continuous aging treatment for 10 minutes or less.

[0005] Patent Document 3 describes a high-strength stainless steel sheet with improved bendability, which is obtained by decarburizing the surface layer of a two-phase structure of ferrite + martensite. Specifically, the high-strength stainless steel sheet has an area ratio of ferrite phase of 48% or more in a thickness cross section within a range of 25 μm from the steel sheet surface in the thickness direction, and an area ratio of ferrite phase of 48% or less in other ranges.

[0006] In addition, Patent Document 4 describes a method for performing a first heat treatment process as a multi-phase heat treatment on a stainless steel sheet, a cold rolling process, and an AC 1 and a second heat treatment step of heating at a temperature below the transformation point.

[0007] Furthermore, Patent Document 5 describes a high-strength stainless steel material in which the difference in hardness between the ferrite phase and the martensite phase is set to 300 HV by carrying out aging treatment after the multi-phase heat treatment, thereby improving bendability. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 63-7338 [Patent Document 2] Japanese Patent Application Publication No. 3-56621 [Patent Document 3] JP 2001-2349290 A [Patent Document 4] JP 2004-323960 A [Patent Document 5] International Publication No. WO2009 / 099035 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the stainless steel that has been subjected to the multi-phase heat treatment under the conditions described in Patent Document 1, cracks may occur when the stainless steel is bent. In addition, while the stainless steel obtained by the manufacturing methods described in Patent Documents 2 to 5 can improve bendability, an additional heat treatment step such as aging treatment must be performed in the manufacturing process after the multi-phase heat treatment. This increases the manufacturing cost.

[0010] An object of one aspect of the present invention is to improve the bendability of duplex stainless steel and reduce the manufacturing costs. [Means for solving the problem]

[0011] In order to solve the above problems, a stainless steel according to one embodiment of the present invention is a stainless steel containing, by mass%, 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.12% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, the stainless steel containing a ferrite phase and a martensite phase and having a hardness of 200 to 340 HV, and in any cross section of the stainless steel, an area fraction of the martensite phase is 60 to 75%, an area fraction of carbides is 0.5 to 1.5%, and the major axis of each of the carbides is 1 μm or less.

[0012] Furthermore, a method for producing a stainless steel according to one embodiment of the present invention includes a final annealing step in which a stainless steel containing, by mass%, 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.12% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, is heated to a temperature range of 800 to 1000°C after a cold rolling step, soaked in the temperature range for less than 1 minute, and then cooled at a cooling rate of 1°C / s or more. Effect of the Invention

[0013] According to one aspect of the present invention, it is possible to improve the bendability of a duplex stainless steel and reduce the manufacturing cost. [Brief description of the drawings]

[0014] [Figure 1] 1 is a SEM photograph of an arbitrary cross section of a duplex stainless steel according to an embodiment of the present invention. [Diagram 2] 1 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the hardness of duplex stainless steel. [Diagram 3] 1 is a graph showing the influence of the holding time at the duplexing temperature and the duplexing temperature on the martensite area ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment of the present invention will be described in detail below. The following description is for better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified. In this specification, "A to B" indicates A or more and B or less. In this specification, "%" regarding chemical composition means "mass %" unless otherwise specified.

[0016] <Terminology> The term "stainless steel" refers to a stainless steel material not limited to a specific shape, and examples of the stainless steel material include steel plates, steel pipes, and bar bars.

[0017] As used herein, unless otherwise specified, "duplex stainless steel" means a stainless steel containing ferritic and martensite phases.

[0018] <General manufacturing method> First, an example of a general manufacturing process for stainless steel strip will be described in outline. In one example, the general manufacturing process for stainless steel strip includes a steelmaking process, a hot rolling process, an annealing process, a pickling process, a cold rolling process, an annealing and pickling process, and a finish rolling process in this order. Each of these steps in the conventional manufacturing process is publicly known, and therefore detailed description thereof will be omitted except for the following description.

[0019] <Summary of the Invention and Findings> Duplex stainless steel has a duplex metal structure consisting of a relatively soft and ductile ferrite phase and a strong martensite phase. Therefore, duplex stainless steel is known as a stainless steel that has both strength and ductility. However, due to the large difference in hardness between the ferrite phase and the martensite phase, duplex stainless steel may concentrate deformation in the soft ferrite phase during bending, causing cracks to occur starting from the ferrite phase.

[0020] In order to improve the bendability, it is conceivable to soften the duplex stainless steel by reducing the phase ratio of the martensite phase in the duplex stainless steel. However, when the phase ratio of the martensite phase is reduced, the phase ratio of the martensite phase that ensures strength is reduced, and the strength of the stainless steel itself is also reduced. In addition, other methods proposed so far for improving the bendability of duplex stainless steel require additional steps such as further heat treatment in the manufacturing process, which increases the manufacturing cost.

[0021] As a result of intensive research, the inventors have found that a high-strength duplex stainless steel with excellent bendability can be obtained by shortening the holding time in the duplex temperature range in the duplex heat treatment (see the examples described later). In the duplex stainless steel of this embodiment, the martensite phase ratio is maintained at a high ratio, and it is not necessary to add a heat treatment step for improving bendability to the series of manufacturing processes. According to one aspect of the present invention, it is possible to provide a duplex stainless steel with high strength and excellent bendability that can be manufactured while reducing the possibility of an increase in manufacturing costs.

[0022] <Duplex stainless steel of the present invention> A duplex stainless steel (stainless steel) according to one embodiment of the present invention includes a ferrite phase and a martensite phase, and has a hardness (Vickers hardness) of 200 to 340 HV, an area ratio of the martensite phase in a cross section of the duplex stainless steel is 60 to 75%, an area ratio of carbides is 0.5 to 1.5%, and a major axis of the carbides is 1 μm or less.

[0023] FIG. 1 is a SEM photograph of a cross section of a duplex stainless steel according to an embodiment of the present invention. As shown in FIG. 1, in a cross section of a duplex stainless steel according to an embodiment of the present invention, carbides can be observed as granular matter dispersed within the material. Examples of carbides present in the duplex stainless steel include (Fe, Cr) 23 C 6and the like. The area ratio of carbide is the ratio of the area where carbide exists (total area of ​​carbide particles) in a given region of the cross section of the duplex stainless steel. The long diameter of carbide means the longest diameter among the diameters of particulate carbide. In the duplex stainless steel of the present invention, the long diameter of each carbide confirmed in the cross section of the duplex stainless steel is 1 μm or less. The direction of the cross section of the duplex stainless steel when measuring the area ratio of martensite phase and carbide, and the long diameter of carbide is not particularly limited. For example, the cross section may be parallel to the rolling direction and plate thickness direction of the duplex stainless steel.

[0024] The duplex stainless steel according to the present embodiment has both ductility and strength by including a ferrite phase having ductility and a martensite phase having strength. The higher the ratio of the hard martensite phase, the higher the strength of the duplex stainless steel itself. However, if the ratio of the martensite phase is excessively high, the ductility of the duplex stainless steel decreases, making processing difficult. Therefore, the area ratio of the martensite phase in the cross section of the duplex stainless steel according to the present embodiment is 60 to 75%. This ensures the strength of the duplex stainless steel itself.

[0025] When duplex stainless steel is bent, its workability decreases if its hardness is high. Also, if its hardness is too low, it is likely to deform when it is used as a product. Therefore, the Vickers hardness of the duplex stainless steel in this embodiment is 200 to 340 HV.

[0026] In duplex stainless steels having the same composition, the difference in the area ratio of carbides in the cross section is considered to be due to the difference in the amount of C dissolved in the martensite phase. That is, in duplex stainless steels having the same composition, the lower the area ratio of carbides, the greater the amount of C dissolved in the martensite phase. If the amount of C dissolved in the martensite phase is large, the hardness of the martensite phase increases, which causes the hardness of the duplex stainless steel itself to increase, adversely affecting the bendability. Therefore, in the duplex stainless steels having the composition of the present invention, the preferred area ratio of carbides in the cross section of the duplex stainless steel is 0.5 to 1.5%.

[0027] Furthermore, in duplex stainless steel, if the carbides are coarse, they are likely to become the starting point of cracks during bending. Therefore, in the duplex stainless steel according to the present embodiment, the major axis of each carbide in the cross section is 1 μm or less, more preferably 0.75 μm or less. This can reduce the possibility of cracks occurring during bending of the duplex stainless steel.

[0028] From the above, a duplex stainless steel with excellent bendability can be realized.

[0029] (composition) The duplex stainless steel according to this embodiment contains, as essential components, in mass%, 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.12% or less N, and 0.01% or less O, with the balance being Fe and unavoidable impurities.

[0030] In addition, the duplex stainless steel according to this embodiment may further contain at least one of the following optional components: 4.0% or less Cu, 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM (rare earth elements). The significance of the content of each element contained in the duplex stainless steel according to this embodiment will be described below.

[0031] C is an austenite-forming element that facilitates the formation of the austenite phase. C stabilizes the austenite structure and improves the strength of the martensite formed during the annealing and / or cooling process. When the C content is high, C increases the volume fraction of the martensite phase and dissolves in the martensite, improving the strength of the stainless steel. Therefore, C is an important element for ensuring the strength of the stainless steel. However, if the C content of the stainless steel is too high, the volume fraction of the martensite phase becomes too high, resulting in a decrease in workability. In addition, if the C content of the stainless steel is too high, it reduces the toughness and corrosion resistance. Therefore, the duplex stainless steel according to this embodiment contains 0.01 to 0.2% C.

[0032] Although Si is an element that has a deoxidizing effect on stainless steel, it is also an element that forms ferrite phase, and therefore if the Si content is high, a sufficient amount of martensite cannot be obtained. On the other hand, excessively low Si content in stainless steel leads to an increase in refining costs. Therefore, the duplex stainless steel according to this embodiment contains 0.01 to 2.0% Si.

[0033] Mn is an austenite-forming element and is effective for obtaining a martensite phase. However, a large amount of Mn content leads to a decrease in workability because the volume fraction of the martensite phase becomes too high. Therefore, the duplex stainless steel according to this embodiment contains 0.1 to 4.0% Mn.

[0034] P and S are unavoidable impurities. Since P and S are elements that reduce toughness, in the duplex stainless steel according to this embodiment, the P content is 0.05% or less and the S content is 0.03% or less.

[0035] Cr is an effective component for improving the corrosion resistance of stainless steel. However, since Cr is a ferrite forming element that facilitates the formation of ferrite phase, if the Cr content of stainless steel becomes too high, the volume fraction of the martensite phase decreases. Therefore, the duplex stainless steel according to this embodiment contains 10.0 to 20.0% Cr.

[0036] Ni is an austenite-forming element and is effective in forming a martensite phase. It is also effective in improving the toughness and corrosion resistance of stainless steel. However, if the Ni content is too high, the stainless steel will be composed of only the martensite phase, and a multi-phase structure will not be obtained. Therefore, the multi-phase stainless steel according to this embodiment has a Ni content of 0.01 to 4.0%.

[0037] N is an element that increases the volume fraction of the martensite phase and contributes to improving the strength of stainless steel. N also improves the strength of stainless steel by dissolving in martensite. However, when the N content is high, the effects of phase ratio control and solid solution strengthening are saturated due to the solubility of N in austenite. Therefore, the duplex stainless steel according to this embodiment has an N content of 0.12% or less. More preferably, the N content is 0.050% or less.

[0038] O is an unavoidable impurity. O forms oxide-based inclusions and is a factor in reducing bendability, so the O content in the duplex stainless steel according to this embodiment is 0.01% or less.

[0039] (Other Ingredients) The duplex stainless steel according to this embodiment may selectively contain one or more elements selected from the following element group in addition to the above essential components.

[0040] Cu is an austenite-forming element and is also effective for maintaining the austenite phase. If Cu is added in excess, the volume fraction of the martensite phase becomes too high, resulting in reduced workability. Therefore, in the duplex stainless steel according to this embodiment, 4.0% or less of Cu may be added as necessary.

[0041] Mo, W, and Co are elements that improve the corrosion resistance of stainless steel. However, if the stainless steel contains excessive amounts of these elements, it becomes hard, its toughness decreases, and the material cost increases. Therefore, in the duplex stainless steel according to this embodiment, one or more of 1.0% or less Mo, 1.0% or less W, and 0.5% or less Co may be added as necessary.

[0042] Al is an effective element as a deoxidizer. However, since Al is a ferrite forming element, if excessive Al is added, it is necessary to increase the amount of austenite forming elements added. Furthermore, the effect of adding Al as a deoxidizer reaches saturation at a certain amount, and does not improve even if it is added in excess. Therefore, the duplex stainless steel according to this embodiment may contain 0.2% or less Al.

[0043] Nb, V, and Ti are elements that have a high affinity with C and N, and are precipitated as carbides or nitrides during hot rolling, which has the effect of improving high-temperature strength. On the other hand, excessive addition of these elements hardens the steel and adversely affects bendability. Therefore, in the duplex stainless steel according to this embodiment, one or more of 1.0% or less Nb, 1.0% or less V, and 1.0% or less Ti may be added as necessary.

[0044] B, Ca, and Mg are elements that improve hot workability and secondary workability. On the other hand, excessive addition of these elements may reduce the manufacturability of stainless steel. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.005% or less of B, 0.005% or less of Ca, and 0.005% or less of Mg may be added as necessary.

[0045] Sn and Sb are elements that improve corrosion resistance. However, excessive addition of these elements may reduce the manufacturability of stainless steel. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.5% or less of Sn and 0.5% or less of Sb may be added as necessary.

[0046] Ga and Ta are elements that improve corrosion resistance. However, excessive addition of these elements may increase the alloy cost. Therefore, in the duplex stainless steel according to the present embodiment, one or more of 0.01% or less Ga and 0.01% or less Ta may be added as necessary.

[0047] Zr, Y, Hf, and REM are elements that improve hot workability and cleanliness of steel. They are also effective as elements for improving oxidation resistance. On the other hand, excessive addition of these elements may increase alloy costs. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM may be added as necessary.

[0048] The balance of the duplex stainless steel according to this embodiment is Fe and unavoidable impurities.

[0049] <Method of manufacturing duplex stainless steel> An example of a method for producing a duplex stainless steel according to an embodiment of the present invention will be described below. The method for producing a duplex stainless steel according to an embodiment of the present invention is characterized in that a duplex heat treatment is performed in the final annealing step in a general method for producing stainless steel.

[0050] (Pretreatment process) In the pretreatment step, first, a vacuum melting furnace is used to produce steel having a composition adjusted to fall within the range of the present invention. This steel is then cast to produce a steel ingot.

[0051] (Hot rolling process) In the hot rolling process, the steel ingot after the pretreatment process is hot rolled to produce a hot rolled steel strip. The temperature in the hot rolling process may be within a general range, for example, about 800 to 1250°C.

[0052] (First annealing process) In the first annealing step, the hot rolled steel strip is annealed (batch annealing) using, for example, a batch annealing furnace (bell annealing furnace). This annealing step is referred to as the first annealing step.

[0053] (pickling process) In the pickling process, the annealed steel strip obtained in the first annealing process is subjected to a pickling treatment in the first pickling process. In this pickling process, a descaling treatment is performed on the annealed steel strip.

[0054] (Cold rolling process) In the cold rolling step, the annealed steel strip descaled in the pickling step is cold rolled at a rolling reduction of, for example, 50 to 90% to form a cold rolled steel strip.

[0055] (Final annealing process) In the method for producing a duplex stainless steel according to the present embodiment, the cold-rolled steel strip cold-rolled by the cold rolling step is subjected to a duplex heat treatment as a final annealing step. Specifically, the cold-rolled steel strip is heated to a duplex temperature range of 800 to 1000°C, preferably 900 to 1000°C, and is soaked in the duplex temperature range for less than 1 minute, preferably 40 seconds or less, and then cooled at a cooling rate of 1°C / s or more, preferably 3°C / s. In the final annealing step, the cold-rolled steel strip is heated to a duplex temperature range of 800 to 1000°C to generate a two-phase metal structure consisting of a ferrite phase and an austenite phase that is transformed into a martensite phase by subsequent cooling. Then, the heated cold-rolled steel strip is cooled at a cooling rate of 1°C / s or more to transform the austenite phase into a martensite phase.

[0056] In this way, in the method for producing a duplex stainless steel according to this embodiment, a two-phase metal structure of ferrite and austenite is produced by a short period (less than 1 minute) of soaking at a temperature of 800 to 1000° C. The cooling rate from the duplex temperature range may be any rate that can transform the austenite phase into the martensite phase.

[0057] In the method for producing the duplex stainless steel according to the present embodiment, the characteristic (short) duplex heat treatment can provide a duplex stainless steel having the desired bendability without the need for any additional heat treatment steps thereafter, and therefore the duplex heat treatment can be used as a final annealing step.

[0058] (Pickling process, finish rolling process) If necessary, the steel strip after the final annealing step is subjected to a final pickling treatment in a pickling step and a finish rolling step.

[0059] As described above, in the manufacturing method of the duplex stainless steel according to one embodiment of the present invention, the cold-rolled steel sheet is heated to a temperature range (duplex temperature range) where the steel sheet is in a two-phase region of ferrite and austenite, and then cooled, in the final annealing step, in which the duplex heat treatment is performed. In the process of the duplex heat treatment, at least a part of the carbides in the cold-rolled steel strip is taken into the austenite phase, and is cooled to be in a state of solid solution in the martensite phase. That is, the duplex heat treatment increases the amount of solute C in the martensite phase of the duplex stainless steel, and the martensite phase is hardened. From this, it is considered that the amount of C solute in the martensite phase of the duplex stainless steel is reduced by shortening the holding time in the duplex temperature range. As a result, it is considered that the hardness of the martensite phase is reduced, the hardness difference with the ferrite phase is reduced, and the hardness of the duplex stainless steel itself is reduced, thereby improving the bendability of the duplex stainless steel.

[0060] (Beneficial Effects) The duplex stainless steel obtained by the above-mentioned exemplary method for producing a duplex stainless steel has excellent bendability.

[0061] Furthermore, the method for producing a duplex stainless steel according to one embodiment of the present invention can produce a duplex stainless steel with excellent bendability without performing an additional heat treatment after the duplex heat treatment, thereby reducing production costs.

[0062] <Example> The results of evaluation of stainless steel sheets according to examples of the present invention (invention examples) and comparative examples will be described below.

[0063] Cold-rolled sheets having a thickness of 2.6 mm were prepared for stainless steels of steel types A to U having the chemical compositions shown in Table 1 below. Steel types A to M are steel types having compositions within the range of the present invention. Steel types N to T are steel types having compositions outside the range of the present invention. The underlined items in Table 1 are items outside the range of the chemical composition of the duplex stainless steel according to one embodiment of the present invention. The same applies to Table 2 below. [Table 1] Next, the steel types A to U were subjected to a final annealing process (multi-phase heat treatment) under the conditions shown in Table 2 below. The annealing time in Table 2 means the soaking holding time at the multi-phase temperature. In Table 2, Nos. 1 to 13 are multi-phase stainless steels of the present invention examples that were subjected to a final annealing process under conditions within the range of the present invention. Nos. 14 to 25 are stainless steels as comparative examples that were subjected to a final annealing process under conditions outside the range of the present invention. Table 2 also shows the results of evaluation of the martensite area ratio, carbide area ratio, carbide diameter (longer diameter of carbide), Vickers hardness and bendability for the present invention examples and comparative examples.

[0064] (volume fraction of martensite phase) The area ratio of the martensite phase in the cross section of each duplex stainless steel sheet obtained by performing the final annealing process under each condition was measured. For each stainless steel sheet, the center of the thickness of the cross section parallel to the rolling direction and plate thickness direction was photographed at 1000x using an optical microscope. The volume ratio of the martensite phase was calculated using the point counting method (JIS G0555) based on the photographed structure photographs. The results are shown in Table 2 under "Martensite area ratio (%)."

[0065] (Carbide area ratio) The area ratio of carbides in the cross section of each duplex stainless steel plate obtained after the final annealing process under each condition was measured. The center of the plate thickness in the cross section parallel to the rolling direction and plate thickness direction of each stainless steel plate was photographed at 2000x using a SEM (scanning electron microscope). The area ratio of carbides was calculated using the point counting method (JIS G0555) based on the backscattered electron images. The results are shown in Table 2 under "Carbide area ratio (%)."

[0066] (longest diameter of carbide) The long diameter of the carbides present in each duplex stainless steel sheet obtained by performing the final annealing process under each condition was measured. The center of the sheet thickness of the cross section parallel to the rolling direction of each stainless steel sheet was photographed at 2000x using an SEM. The long diameter of the largest carbide in the photographed backscattered electron image was measured, and the results are shown in Table 2 under "Carbide diameter (μm)."

[0067] (Vickers hardness) The Vickers hardness of each of the duplex stainless steel sheets obtained by the final annealing process under each condition was measured using a Vickers hardness tester with a test load of 5 kg in accordance with JIS Z2244. The evaluation results are shown in Table 2 under "Vickers hardness (HV)."

[0068] (bendability) A bending test was carried out on the duplex stainless steel sheets obtained by the final annealing process under each condition in order to evaluate the bendability of each duplex stainless steel sheet. A sample piece of 40 mm (rolling direction) x 150 mm (sheet width direction) was taken from the duplex stainless steel sheet obtained by the final annealing process under each condition. The sample piece was pressed against a V-block jig with a tip of 2.5R and a tip angle of 90° so that the bending ridge was parallel to the rolling direction, and a 90° bending process was carried out. The bending ridge was observed at a magnification of 50 times using a microscope to confirm the presence or absence of cracks. "◯" indicates that no cracks were generated, and "×" indicates that cracks were generated. [Table 2] As shown in Table 2, inventive examples No. 1 to No. 13 obtained by performing a final annealing process under conditions within the range of the present invention, the martensite area ratio, carbide diameter, and Vickers hardness were within the ranges specified in the present invention, and they had good bendability.

[0069] On the other hand, in Comparative Examples 14 to 25 in which the final annealing step was performed under conditions outside the scope of the present invention, any one of the martensite area ratio, carbide diameter, and Vickers hardness was outside the scope of the present invention, and the bendability was evaluated as poor. In Comparative Examples 14 and 17 to 20, the bendability was evaluated as good, but the martensite area ratio was outside the scope of the present invention. In other words, it is considered that the strength of the duplex stainless steel was not ensured.

[0070] As an example showing the effect of different annealing times, Example No. 9 of the present invention and Example No. 16 of the comparative example are compared. Example No. 9 of the present invention and Example No. 16 of the comparative example are the same steel type I and are subjected to the same multi-phase heat treatment at the same multi-phase temperature, but the annealing times are different. Since the multi-phase temperature is the same, the martensite area ratio of the two examples is the same, but Example No. 16, which has an annealing time of more than 1 minute, has increased hardness and poor bendability. This is thought to be because the carbide area ratio of Example No. 9 is 0.52%, while that of Example No. 16 is 0.23%, and therefore more carbides are dissolved in the martensite phase in Example No. 16, resulting in an increased hardness of the martensite phase.

[0071] (Effect of holding time at duplex temperature and duplex temperature on hardness of duplex stainless steel) 2 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the hardness of duplex stainless steel. The Vickers hardness of the duplex stainless steel was measured when the holding time was 40 seconds and 90 seconds for a steel plate having the composition of the above steel type I, and the duplexing temperature was changed from 900 to 1100°C. The Vickers hardness was measured according to the method described above. Regarding the holding time, 40 seconds is within the range of the present invention, and 90 seconds is outside the range of the present invention.

[0072] 2, when stainless steels having the same composition are subjected to the same duplexing temperature within the duplexing temperature range of the present invention (900 to 1000°C), the Vickers hardness is lower when the holding time at the duplexing temperature is 40 seconds. Also, when the holding time at the duplexing temperature is 90 seconds, the hardness already exceeds 340HV at a duplexing temperature of 1000°C.

[0073] This experiment demonstrated that by setting the holding time at the duplex temperature within the duplex temperature range of the present invention to less than 1 minute, a duplex stainless steel having excellent bendability and a hardness of 200 to 340 HV can be obtained.

[0074] (Effect of holding time at duplex temperature and duplex temperature on martensite area ratio) 3 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the martensite area ratio of duplex stainless steel. For a steel plate having the composition of steel type I, the holding time was 40 seconds and 90 seconds, and the duplexing temperature was changed from 900 to 1100°C, and the martensite area ratio was measured. The measurement of the martensite area ratio was carried out according to the method described above.

[0075] From Figure 3, it can be seen that the change in martensite area ratio due to the change in the duplexing temperature is similar when the holding time at the duplexing temperature is 40 seconds and when it is 90 seconds. In other words, it has become clear that the martensite area ratio of duplex stainless steel is determined by the duplexing temperature, not by the holding time at the duplexing temperature.

[0076] [Additional Notes] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

Claims

1. A stainless steel containing, by mass%, 0.01 to 0.122% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.12% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities; Contains ferrite and martensite phases, The hardness is 200 to 340 HV. In any cross section of the stainless steel, an area ratio of the martensite phase is 60 to 75%, an area ratio of carbides is 0.5 to 1.5%, and the major axis of each of the carbides is 1 μm or less.

2. A stainless steel containing, by mass%, 0.01-0.122% C, 0.01-2.0% Si, 0.1-4.0% Mn, 0.05% or less P, 0.03% or less S, 10-20% Cr, 0.01-4.0% Ni, 0.12% or less N, 0.01% or less O, 4.0% or less Cu, with the balance being Fe and unavoidable impurities, Contains ferrite and martensite phases, The hardness is 200 to 335 HV. In any cross section of the stainless steel, an area ratio of the martensite phase is 60 to 75%, an area ratio of carbides is 0.5 to 1.5%, and the major axis of each of the carbides is 1 μm or less.

3. 3. The stainless steel according to claim 1 or 2, further containing, by mass%, at least one of the following: 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM.

4. The stainless steel contains, by mass%, 0.01 to 0.122% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.12% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, and includes a final annealing step in which the stainless steel is heated to a temperature range of 800 to 1000°C after a cold rolling step, soaked in the temperature range for less than 1 minute, and then cooled at a cooling rate of 1°C / s or more; The stainless steel after the final annealing step includes a ferrite phase and a martensite phase, The hardness is 200 to 340 HV. In any cross section of the stainless steel after the final annealing step, the area ratio of the martensite phase is 60 to 75%, the area ratio of carbides is 0.5 to 1.5%, and the major axis of the carbides is 1 μm or less.

5. A stainless steel containing, by mass%, 0.01-0.122% C, 0.01-2.0% Si, 0.1-4.0% Mn, 0.05% or less P, 0.03% or less S, 10-20% Cr, 0.01-4.0% Ni, 0.12% or less N, 0.01% or less O, 4.0% or less Cu, with the balance being Fe and unavoidable impurities, the stainless steel being heated to a temperature range of 800-1000°C after a cold rolling process, and being held at the same temperature range for less than 1 minute, followed by a final annealing process of cooling at a cooling rate of 1°C / s or more; The stainless steel after the final annealing step includes a ferrite phase and a martensite phase, The hardness is 200 to 335 HV. In any cross section of the stainless steel after the final annealing step, the area ratio of the martensite phase is 60 to 75%, the area ratio of carbides is 0.5 to 1.5%, and the major axis of the carbides is 1 μm or less.

6. A method for producing a stainless steel as described in claim 4 or 5, further containing, by mass%, at least one of the following: 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM.

Citation Information

Patent Citations

  • Production of composite phase structure chromium stainless steel sheet or steel strip having small intrasurface anisotropy and high ductility and high strength

    JP1988007338A

  • Production of chromium stainless steel strip of double phase structure having small intra-surface anisotropy and high ductility and high strength

    JP1988169334A

  • Production of high strength dual phase stainless steel strip excellent in spring characteristic

    JP1991056621A

  • Stainless steel material for metal gasket excellent in setting resistance and its manufacture

    JP2000256802A

  • JP2001-2349290A